One-step fabrication of silver nanosphere-wetted carbon nanotube electrodes via electric-field-driven combustion waves for high-performance flexible supercapacitors. Issue 15 (26th March 2019) - Yeo, Taehan; Lee, Jaeho; Shin, Dongjoon; Park, Seonghyun; Hwang, Hayoung; Choi, Wonjoon
Abstract : Electric-field driven combustion waves yield completely wetted hybrids of single-crystalline, spherical Ag particles and multi-walled carbon nanotubes for high-performance supercapacitors. Abstract : Hybrids of micro/nanostructured metals/metal oxides and carbon-based materials are promising candidates for electrochemical electrodes. However, their fabrication requires complex procedures involving the interfaces and grain boundaries between constituent materials that degrade the overall performances. Herein, we report one-step electric-field driven combustion waves to fabricate the completely wetted hybrids of single-crystalline, spherical silver micro/nanoparticles and carbon nanotube webs, thereby significantly improving the contact interfaces and reducing the grain boundaries. The electric fields across the layered films of nitrocellulose, silver oxide nanoparticles and carbon nanotubes enable the combustion waves of ultrafast heating–cooling which facilitates the relocation of reduced and liquefied silver along the fiber-like networks and formation of single-crystalline silver particles, while the carbon nanotubes were mostly preserved without oxidization. These hybrids exhibited outstanding specific capacitance (1083 F g −1 ) and capacitance retention (95% after 10 000 cycles) as supercapacitor electrodes. Furthermore, the symmetric/solid-state/flexible supercapacitors using the electrodes showed remarkable electrochemical performances (458 F g −1, 100% after 10 000 cycles) and stability under harsh mechanical strains, such as bending and twisting (∼97%). This fabrication strategy enables scalable synthesis processes for functional hybrids having unique interfacial and grain boundaries.